Encoding type, medication, and deep brain stimulation differentially affect memory-guided sequential reaching movements in Parkinson's disease - David, Fabian J.; Rivera, Yessenia M.; Entezar, Tara K.; Arora, Rishabh; Drane, Quentin H.; Munoz, Miranda J.; Rosenow, Joshua M.; Sani, Sepehr B.; Pal, Gian D.; Verhagen-Metman, Leonard; Corcos, Daniel M. (Frontiers in Neurology, 2022)
Memory-guided movements, vital to daily activities, are especially impaired in Parkinson’s disease (PD). However, studies examining the effects of how information is encoded in memory and the effects of common treatments of PD, such as medication and subthalamic nucleus deep brain stimulation (STN-DBS), on memory-guided movements are uncommon and their findings are equivocal. We designed two memory-guided sequential reaching tasks, peripheral-vision or proprioception encoded, to investigate the effects of encoding type (peripheral-vision versus proprioception), medication (on- versus off-), STN-DBS (on- versus off-, while off-medication), and compared STN-DBS versus medication on reaching amplitude, error, and velocity. We collected data from 16 (analyzed n=7) participants with PD, pre- and post-STN-DBS surgery, and 17 (analyzed n=14) healthy controls. We had four important findings. First, encoding type differentially affected reaching performance: peripheral-vision reaches were faster and more accurate. Also, encoding type differentially affected reaching deficits in PD compared to healthy controls: peripheral-vision reaches manifested larger deficits in amplitude. Second, the effect of medication depended on encoding type: medication had no effect on amplitude, but reduced error for both encoding types, and increased velocity only during peripheral-vision encoding. Third, the effect of STN-DBS depended on encoding type: STN-DBS increased amplitude for both encoding types, increased error during proprioception encoding, and increased velocity for both encoding types. Fourth, STN-DBS was superior to medication with respect to increasing amplitude and velocity, whereas medication was superior to STN-DBS with respect to reducing error. We discuss our findings in the context of the previous literature and consider mechanisms for the differential effects of medication and STN-DBS.